Teknologi Ekonomi Kreatif, Upaya Memanfaatkan Limbah Kulit Kerang Memiliki Nilai Ekonomi Tinggi Di Desa Karang Suraga Kecamatan Cinangka - Euis Amilia (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2019)
The aim of the Student Work Lecture (KKM) in 2019, about Creative Economy Technology is to improve the skills of the village community in Karang Suraga Village, especially housewives, village youths and students of SMK 1 Cinangka. The partners of this activity are non-productive communities in Karang Suraga village, Kec. Cinangka. The problem faced is not yet knowing the use of conch shells to produce useful products and have a sale value. The method of implementing this service is through (1) Surveying through observations, interviews, and analysis of village problems and potentials, (2) Training on shellfish creativity. The result of this program is the increase in community knowledge and skills regarding shellfish waste treatment. This program is expected to facilitate the community in increasing their knowledge and skills in processing used materials into useful products and selling values, so that Karang Suraga a villager become productive communities.